Pityriasis rosea preferentially localized to a port-wine stain. - Magri Gatt, P.; Boffa, M.M.; Mintoff, D.; Boffa, M.J. (European Journal of Pediatric Dermatology, 2023)
We present an unusual case of pityriasis rosea (PR) in a 9-year-old girl who was affected by a port-wine stain (PWS) of the left hemithorax since birth. PR lesions prevailed on the PWS, respecting its borders, but also poorly involved the opposite side of the trunk. To our knowledge, similar cases of PR preferentially localized on a PWS have not previously been reported in the literature.